Design, Fabrication & Testing of a Low-Power Electric Thruster for Nanosatellite Missions - Jaeger-Letts, Zoe (Wellington Faculty of Engineering Symposium, 2023)
Nanosatellites like the CubeSat standard provide low-cost and adaptable platforms for fast design iteration and enable the testing of new and disruptive technologies in space. Despite their merits, the nanosatellite platform imposes stringent mass and volumetric limitations, which has typically seen such missions constrained to passive, Low Earth orbit missions. However, these previously accepted limitations of small spacecraft are being actively challenged by recent developments in miniaturized electric propulsion technology. Electric thrusters deliver low thrust compared to traditional chemical rockets but provide distinct advantages due to their highly efficient consumption of propellant. Advancements in electric propulsion is opening horizons for more ambitious nanosatellite in-orbit manoeuvres, advanced satellite constellation networks, and space exploration outside Earth's sphere of gravitational influence. Inspection of electric propulsion literature highlighted a distinct lack of understanding and developmental work on low-power, miniaturised electric thruster technology. Furthermore, the scalability and operational performance of these low-power thrusters has not been conclusively explored. Resultantly, there is an absence of efficient and reliable electric thrusters that can support ambitious nanosatellite missions. The work presented in this paper fills this gap in knowledge by first presenting a background on electric propulsion theory and thruster scaling, before outlining a thruster design methodology. Operational data from the artefact thruster and an evaluation of the system's performance against standard electric propulsion metrics like thrust, efficiency, and specific impulse is also presented.